Sikap Tokoh Masyarakat dalam Mewujudkan Desa Siaga Aktif - Hardika, Mufida Dian; Sari, Wida Rahma Arwiyanta; Uma, Elita Chobi Batul (FORIKES, 2024)
Community participation in active alert village activities has not gone well, giving rise to the problem of still high maternal mortality rates. This research aimed to determine the attitudes of community leaders towards empowerment activities and community participation in creating an active alert village in Candimulyo Village, Dolopo District, Madiun Regency. This research was a descriptive study, involving 32 human resources implementing community participation empowerment, namely village heads, village officials, community leaders, religious leaders, posyandu cadres, dasa homesteads, youth organizations and other elements, who were selected using a total sampling technique. The instrument used to measure attitudes was a questionnaire with closed questions. Data were analyzed using descriptive statistical methods in the form of frequencies and proportions. The results of the research showed that supportive attitudes for each activity were as follows: approach activities = 53.13%, socialization activities = 50%, village community forum activities = 37.5%, introspective survey activities = 43.75%, activities village community deliberation = 56.25%, planning activities = 28.13%, and village health post activities = 53.13%. The research conclusion shows that the attitude of community leaders towards their participation in active alert village activities is in the medium category.Keywords: attitude; community participation; the village is on active alert ABSTRAK Peran serta masyarakat terhadap kegiatan desa siaga aktif belum berjalan dengan baik, sehingga menimbulkan masalah masih tingginya angka kematian ibu. Penelitian ini bertujuan untuk mengetahui sikap tokoh masyarakat terhadap kegiatan pemberdayaan peran serta masyarakat dalam mewujudkan desa siaga aktif di Desa Candimulyo, Kecamatan Dolopo, Kabupaten Madiun. Penelitian ini merupakan studi deskriptif, yang melibatkan 32 sumberdaya manusia pelaksana pemberdayaan peran serta masyarakat yaitu kepala desa, perangkat desa, tokoh masyarakat, tokoh agama, kader posyandu, dasa wisma, karang taruna dan unsur lainnya, yang dipilih dengan teknik total sampling. Instrumen yang digunakan untuk pengukuran sikap adalah kuesioner dengan pertanyaan tertutup. Data dianalisis menggunakan metode statistika deskriptif berupa frekuensi dan proporsi. Hasil penelitian menunjukkan bahwa sikap mendukung untuk masing-masing kegiatan adalah sebagai berikut: kegiatan pendekatan = 53,13%, kegiatan sosialisasi = 50%, kegiatan forum masyarakat desa = 37,5%, kegiatan survei mawas diri = 43,75%, kegiatan musyawarah masyarakat desa = 56,25%, kegiatan perencanaan = 28,13%, serta kegiatan pos kesehatan desa = 53,13%. Kesimpulan penelitian menunjukkkan bahwa sikap tokoh masyarakat terhadap peran sertanya dalam kegiatan desa siaga aktif adalah dalam kategori sedang.Kata kunci: sikap; peran serta masyarakat; desa siaga aktif